INHIBITION OF INFLUENZA VIRUS MULTIPLICATION BY ALKYL DERIVATIVES OF BENZIMIDAZOLE : I. KINETIC ASPECTS OF INHIBITION BY 2,5-DIMETHYLBENZIMIDAZOLE AS MEASURED BY INFECTIVITY TITRATIONS - Tamm, Igor (The Rockefeller University Press, 1953)
At a concentration of 0.0026 M, 2,5-dimethylbenzimidazole caused a number of alterations in the first cycle of multiplication of influenza B virus, Lee strain, in chorioallantoic membrane cultures in vitro. As determined by infectivity titrations in ovo on the membrane per se, the following alterations were observed: The duration of the latent period was increased by 80 per cent. The rate of increase in titer during the incremental period was somewhat decreased. The yield of virus was decreased by about 99 per cent. When the compound was added to membrane cultures at various periods before or after inoculation with the virus, the following findings were obtained: On addition before or along with the virus, the substance caused about 99 per cent inhibition of multiplication. When added during the first 2 hours after inoculation, the compound caused inhibition of a degree which was inversely proportional to the time of addition. When added 3 to 8 hours after inoculation, the substance caused about 80 per cent inhibition. When added after the end of the latent period, no definite inhibition was obtained in the first cycle of multiplication. These results are interpreted as indicating that 2,5-dimethylbenzimidazole acts by reducing the rate of biosynthetic mechanisms necessary for the reproduction of influenza virus particles.